Solution chemistry and anti-proliferative activity against glioblastoma cells of a vanadium(V) complex with two bioactive ligands - Levina, Aviva; Scalese, Gonzalo; Gambino, Dinorah; Crans, Debbie C.; Lay, Peter A. (Frontiers in Chemical Biology, 2024)
Introduction: Glioblastoma is a brain cancer difficult to treat but recently mixed-ligand vanadium(V) Schiff base/catecholato complexes have exhibited high in vitro anti-proliferative activity. Hence, we explored the activity of [VVOL1L2], which contains two iron chelating ligands, 2-hydroxy-1-naphthylaldehyde iso-nicotinoyhydrazone (L1H2) and clioquinol (L2H). This complex was previously reported to be very effective against Trypanosoma cruzi, the causative agent of Chagas disease. These studies explored the possibility that a compound with efficacy against Trypanosoma cruzi also has efficacy against human glioblastoma cancer cells. Since [VVOL1L2] was poorly soluble in water and the clioquinol ligand dissociated from the complex upon addition to an aqueous environment, an understanding of the speciation was very important to interpret its biological activity. Methods: Stability studies in cell media were followed by UV/Vis spectroscopy to determine speciation of relevance to the in vitro anti-proliferative activity of the complex with T98G glioblastoma cells, which was also measured in the absence and presence of Fe(III). Results and Discussion: The current work demonstrated that the mixed-ligand vanadium coordination complex had high in vitro anti-proliferative activity against the human glioblastoma (T98G) cell line. The enhanced anti-proliferative effects of the mixed-ligand vanadium complex against T98G cells could be due to either hydrolysis of complex and release of the toxic clioquinol, or the rapid uptake of the lipophilic complex prior to hydrolysis. The speciation studies showed that at least part of the potent toxicity of the mixed-ligand coordination complex stemmed from release of the bioactive clioquinol ligand from the complex, which depended on whether Fe(III) was present. The studies also showed that the [VV(O)2 (L1H)] coordination complex was the most potent complex that remained intact and, hence, the complex that is the most biological active. Thus, future development of complexes should focus on the one-ligand intact complexes or making any mixed-ligand complex more water soluble, stable in aqueous solution, or designed to be rapidly taken up by diseased cells prior to hydrolysis.